MENAKAR WORK FROM EVERYWHERE DI ERA NEW NORMAL - Hartanto, Rudi; Sanica, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.06.TAHUN.2021, 2021)
This study aims to add literature by studying the implementation of work from everywhere in government offices and their impact on civil servants. The study was conducted with interviews with resource persons who run work from everywhere (data collection), data reduction (data reduction), presentation of data (display data), and drawing/presentation of conclusions (conclusion drawing/verification). The results of the study showed that First, the function of the organization continues to run well. Second, civil servants have no difficulty carrying out work from everywhere and can fully work at home or elsewhere. Third, the importance of integrity and professionalism supervision on the implementation of work from everywhere where the impact caused by lack of integrity and professionalism on public servants is harmful to the organization. Surveillance can be input monitoring and behavioral monitoring. Fourth, civil servants do not fully agree that work from everywhere is done as a new normal after the pandemic ends. Public servants want to work from the office rather than work from everywhere. Fifth, leadership does not experience significant obstacles in the implementation of work from everywhere.